Biodynamical aspects of running speed development - Coh, M. (2nd International scientific conference: Exercise and quality of life, Novi Sad. March 24/26th 2011, 2011)
Maximum speed, which is produced during movement, depends on various factors. These factors are related to morphological and physiological characteristics, energetic mechanisms, age, gender, motor abilities, inter- and intra-muscular coordination and optimal biomechanical technique of movement. Locomotive speed in the form of sprinting is one of the most important abilities, which defines the successfulness of athletes in many sport disciplines. From the genetic (hereditary) motor programme aspect, speed can be classified into primary phylogenetic human movements. In specific sports situations, speed is being manifested in a form of the »three-segment model«. The model consists of speed, strength and coordination. Pondering of individual segments of this model depends on the particularities of specific sport disciplines. Maximum running speed is a product of the frequency and the length of stride. Both variables are mutually dependant; they are also linked to the processes of central regulation of movement, to the morphological characteristics, motor abilities and energetic processes. The relationship between the frequency and the length of a stride is individually defined and automated. Changing one variable results in changes of the second. When a length of a stride is increased, the frequency decreases and vice versa.